Post-Acute Sequelae of COVID-19: What to do Next? - Anila Jaleel (ziauddin University, 2024)
The world suffered from the COVID-19 pandemic from December 2019 to date which results in the loss of many precious human lives. This creates a sense of insecurity and depression among those who lived without their loved ones. The first case of COVID-19 was reported in Pakistan in February 2020 which results in people being in quarantine for several months. Outdoor activities were closed and people had to work and study from home. Pakistan's government was able to manage the pandemic well and less mortality was reported compared to developed countries.